A c-type lectin HcLec1 with dual function of immunology and mineralization from the freshwater oyster (Hyriopsis cumingii Lea) - Xiaofeng Chen; Xiaoya Shen; Shijun Liu; Wenjuan Li; Wenjuan Li; He Wang; Jiale Li; Jiale Li; Zhiyi Bai; Zhiyi Bai (Frontiers in Immunology)
BackgroundShell and pearl formation in bivalves is a sophisticated biomineralization process that encompasses immunological and mineralization aspects, particularly during shell repair and the initial stages of pearl cultivation when a nucleus is inserted. Here, we describe a novel C-type lectin, HcLec1, isolated and characterized from the freshwater pearl mussel Hyriopsis cumingii Lea. MethodsImmune challenge, RNA interference (RNAi) experiments, ELISA, and antibacterial assays were employed to investigate the role of HcLec1 in innate immunity. We also established shell damage repair and pearl nucleus insertion models to examine the impact of HcLec1 on the biomineralization process in Hyriopsis cumingii Lea. In vitro calcium carbonate crystallization assays were conducted to explore the direct role of HcLec1 in calcium carbonate crystal formation.ResultsThe HcLec1 gene sequence is a full-length cDNA of 1552 bp, encoding 240 amino acids. HcLec1 comprises an N-terminal signal peptide and a carbohydrate-recognition domain (CRD), with QPD (Gln-Pro-Asp) and MND (Met-Asn-Asp) motifs for polysaccharide binding. Tissue expression analysis showed that HcLec1 is predominantly expressed in the gill tissue of Hyriopsis cumingii Lea under normal conditions, and its expression is significantly elevated in both gill and pearl sac tissues following nucleus insertion for pearl cultivation (P < 0.05). After immune stimulation with Aeromonas hydrophila and lipopolysaccharides (LPS), HcLec1 expression levels significantly increased in both cases (P < 0.01), indicating a role in bivalve innate immunity. RNA interference (RNAi)-mediated knockdown of HcLec1 led to a significant decrease in the expression levels of immune-related genes (WAP, α2m, and Lyso) and mineralization-related genes (CA, CHS, Nacrein, and Pif) (P < 0.05). In animal models for shell damage and nucleus insertion in pearl cultivation, HcLec1 showed a consistent expression pattern, with an initial significant decrease followed by a marked increase, peaking at day 14 (P < 0.05). This suggests a role for HcLec1 in pearl formation and shell repair. The recombinant HcLec1 protein demonstrated binding affinity to LPS and PGN, a robust ability to agglutinate Escherichia coli, Staphylococcus aureus, Aeromonas veronii, and Aeromonas hydrophila, and significantly inhibited bacterial growth (P < 0.05). Moreover, rHcLec1 promoted calcite crystal formation in saturated calcium carbonate solutions and altered crystal morphology.DiscussionThe HcLec1 gene plays a pivotal role in both innate immunity and biomineralization in the triangle sail mussel. This study enhances our understanding of the functional diversity of C-type lectins and provides a foundation for future studies on shell repair and pearl growth.